Implications of oxidovanadium(IV) binding to actin - Ramos, Susana (2012)
Oxidovanadium(IV), a cationic species (VO2+) of vanadium(IV), binds to several proteins, including actin. Upon titration with oxidovanadium(IV), approximately 100% quenching of the intrinsic fluorescence of monomeric actin purified from rabbit skeletal muscle (G-actin) was observed, with a V50 of 131 μM, whereas for the polymerized form of actin (F-actin) 75% of quenching was obtained and a V50 value of 320 μM. Stern– Volmer plots were used to estimate an oxidovanadium(IV)-actin dissociation constant, with Kd of 8.2 μM and 64.1 μM VOSO4, for G-actin and F-actin, respectively. These studies reveal the presence of a high affinity binding site for oxidovanadium(IV) in actin, producing local conformational changes near the tryptophans most accessible to water in the three-dimensional structure of actin. The actin conformational changes, also confirmed by 1H NMR, are accompanied by changes in G-actin hydrophobic surface, but not in F-actin. The 1H NMR spectra of G-actin treated with oxidovanadium(IV) clearly indicates changes in the resonances ascribed to methyl group and aliphatic regions as well as to aromatics and peptide-bond amide region. In parallel, it was verified that oxidovanadium(IV) prevents the G-actin polymerization into F-actin. In the 0–200 μMrange, VOSO4 inhibits 40% of the extent of polymerization with an IC50 of 15.1 μM, whereas 500 μM VOSO4 totally suppresses actin polymerization. The data strongly suggest that oxidovanadium(IV) binds to actin at specific binding sites preventing actin polymerization. By affecting actin structure and function, oxidovanadium(IV) might be responsible for many cellular effects described for vanadium.